The salience of enhanced components within inharmonic complexes - Byrne, Andrew J. (Acoustical Society of America, 2013)
A subjective listening task was used to measure the salience of enhanced components using typical intensity-enhancement stimuli, time-reversed versions of those stimuli, and stimuli which contained a frequency shift of the target component. Twenty-five listeners judged whether or not a pitch “stood out” within an inharmonic complex. For comparison, judgments also were made for stimuli with a single segment that consisted of a simultaneously masked target. The results indicate that the perceived salience of enhanced components is greater than might be predicted by the effective magnitude of those components, and that informational masking is likely involved.